Understanding Structural Divergence in European Manufacturing - Livio Romano (Intereconomics, 2016)
The heterogeneity among European manufacturing systems has widened in the last 15 years under the competitive pressure of new industrial powers within and outside the EU boundaries and as a result of the 2008 global recession. This paper describes this transformation, in terms of the sectoral composition and the geographical concentration of industrial activities. It also analyses how cross-country differences in export performance, in the dynamics of domestic demand and in the exposure to low-cost import competition have contributed to the divergence in fortunes in European manufacturing.
Keywords: 330